Food neophobia and ethnic food consumption intention An extension of the theory of planned behaviour - Hiram, Ting; Ernest Cyril, de Run; Cheah, Jun-Hwa; Chuah, Francis (Emerald Group Publishing Limited, 2016)
Purpose – The purpose of this paper is to serve as groundwork to investigate the determinants of ethnic food consumption intention in the context of developing markets. Using the theory of planned behaviour as the underlying basis, it is aimed to explain the effect of attitude, subjective norm and perceived behaviour control on consumption intention towards Dayak food. Since Dayak food is relatively unfamiliar compared to conventional food in Malaysia, food neophobia is incorporated into the model so as to assess its moderation effect on every postulated relationship. Design/methodology/approach – A quantitative approach via self-administered questionnaire was adopted. In all, 300 copies of the questionnaire were distributed to non-Dayak Malaysians, and 211 usable copies were subsequently collected, suggesting that non-response bias was not a major issue. A post hoc Harman single-factor analysis was also performed to ensure the variance in the data was not explained by one single factor, thus addressing the common method bias. Structural equation modelling using partial least squares approach was then utilized to assess the relationships of variables under investigation and the moderation effect of food neophobia. Findings – After ensuring the data have acceptable reliability and validity, structural model assessment was performed to test the hypotheses. The findings show that attitude, subjective norm and perceived behavioural control all have positive effect on consumption intention of non-Dayak Malaysians towards Dayak food. However, food neophobia is only found to have a moderation effect on the relationship between subjective norm and consumption intention. Research limitations/implications – First, the sample is largely consisted of college and university students in Malaysia who are believed to be more daring to try new things, including new food. Second and more importantly, the dearth of literature and empirical studies on Dayak food and ethnic food in Malaysia might have actually pointed to the limitation in using only quantitative questionnaire in the study. As salient beliefs are the antecedents in the theory of planned behaviour, knowing consumers’ specific beliefs about Dayak food would have provided a more detailed and comprehensive understanding of consumption intention and the moderating effect of food neophobia